Spatiotemporal distribution of physicochemical parameters and toxic elements in Lake Pomacochas , Amazonas, Peru - Leiva-Tafur, Damaris; Goñas, Malluri; Culqui, Lorenzo; Santa Cruz, Carlos; Rascón, Jesús; Oliva-Cruz, Manuel (Frontiers in Environmental Science, 2022)
Lakes are water bodies that play an essential role as water sources for humanity, as they provide a wide range of ecosystem services. Therefore, this study aimed to evaluate Pomacochas Lake, a high Andean lake in the north of Peru. A variety of parameters were studied including, the concentrations of physicochemical parameters such as temperature (T °C), dissolved oxygen (DO), potential hydrogen (pH), electrical conductivity (EC), turbidity, total dissolved solids (TDS), biochemical oxygen demand (BOD), alkalinity, chlorides hardness, nitrates, nitrites, sulfates, ammonium, elements such as aluminum (Al), calcium (Ca), magnesium (Mg), sodium (Na), potassium (K), and boron (B), as well as metals and metalloids such as zinc (Zn), cadmium (Cd), copper (Cu), lead (Pb), and arsenic (As). In addition, pH, Zn, and Cu were evaluated at the sediment level. It is important to note that all parameters evaluated in the water matrix showed significant differences in the seasonal period and depth levels. In comparison, the parameters evaluated at the sediment level had no significant differences between the seasonal period and sampling points. As for the seasonal period, the variables that were higher for the dry season were EC, TDS and Pb, while for the wet season were BOD, Zn, Mg, turbidity, Ca, DO, T and pH. At the depth levels, parameters such as TDS, Pb and As had similar behavior for the three depths evaluated. According to national standards, latent contamination by Cd and Pb was found in the lake water from the ecological risk assessment. However, by international standards, all sampling stations showed a high level of contamination by Cd, Pb, Zn, Cu and As, which represents a potential risk for the development of socio-economic activities in the lake. At the same time, the evaluation of sediments did not present any potential risk.